2007
DOI: 10.1007/s11239-007-0074-0
|View full text |Cite
|
Sign up to set email alerts
|

Higher morning serum cortisol level predicts increased fibrinogen but not shortened APTT

Abstract: The results of this retrospective investigation confirm that baseline cortisol levels might predict higher fibrinogen in the general population. This potential biological interrelationship deserves further scrutiny for the potential implications on prediction and prevention of the cardiovascular risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 8 publications
0
14
0
Order By: Relevance
“…Furthermore, the results highlight the protective role an 8-h sleep opportunity between shifts of simulated firefighting work has on preserving normal cortisol levels when compared to a 4-h sleep opportunity. Given the number of adverse health outcomes associated with chronically high cortisol levels (Lippi et al 2008;Mackin and Young 2004;Rosmond et al 2003;Silverman and Sternberg 2012), future research should examine how prolonged exposure to firefighting work and restricted sleep (e.g. long or multiple deployments over a fire season) affects firefighters' cortisol levels in the medium to longer term.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the results highlight the protective role an 8-h sleep opportunity between shifts of simulated firefighting work has on preserving normal cortisol levels when compared to a 4-h sleep opportunity. Given the number of adverse health outcomes associated with chronically high cortisol levels (Lippi et al 2008;Mackin and Young 2004;Rosmond et al 2003;Silverman and Sternberg 2012), future research should examine how prolonged exposure to firefighting work and restricted sleep (e.g. long or multiple deployments over a fire season) affects firefighters' cortisol levels in the medium to longer term.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, heart disease is the leading cause of on-duty death among firefighters (Kales et al 2007). Given the association between chronically elevated cortisol and CVD (Lippi et al 2008;Rosmond et al 2003) and other adverse health effects (e.g. mood disorders; Mackin and Young 2004), these findings draw further attention to the need for research that investigates the effects of longer and chronic exposure to wildland firefighting work and restricted sleep on long-term cortisol levels.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…There is a strong statistical correlation between moderate to high levels of chronic psychological stress over extended periods, elevated plasma fibrinogen concentration, and CVD in various studies [30][31][32][33].…”
Section: Chronic Stress and Elevated Fibrinogenmentioning
confidence: 99%
“…Lippi et al studied the morning serum cortisol and fibrinogen levels in 302 patients and found a strong statistical relationship between elevated levels of both inflammatory markers [30]. They found morning cortisol levels that were higher on the reference parameters equated with higher fibrinogen levels [33].…”
Section: Interventionmentioning
confidence: 99%